Pengaruh Beban Kerja dan Stres Kerja terhadap Burnout Pada Pegawai Salah Satu Instansi Pemerintah di Kota Bandung - Farhan Nurkholis Sabiq; Andhika Mochamad Siddiq; Arie Hendra Saputro (IKRAITH-EKONOMIKA, 2026)
The growing incidence of employee overtime, particularly involving prolonged working hours, has become an important organizational concern because insufficient recovery opportunities may contribute to both physical and psychological exhaustion. Against this background, the present study examined the levels of burnout, workload, and work stress, while also evaluating the effects of workload and work stress on burnout among employees of a government institution in Bandung. A quantitative approach was employed by collecting questionnaire responses from 100 employees. The research data were processed using multiple linear regression analysis. The findings revealed that burnout, workload, and work stress were generally classified as moderately high. Regression testing further demonstrated that workload and work stress each had a positive and statistically significant relationship with burnout (p < 0.05). When analyzed simultaneously, both independent variables also exhibited a significant combined contribution to burnout. The regression model produced an Adjusted R Square value of 0.735, indicating that workload and work stress accounted for 73.5% of the variation in burnout, whereas the remaining 26.5% was associated with variables not incorporated into the present study. Overall, the findings suggest that increases in workload and work stress are likely to be accompanied by higher levels of employee burnout. These results highlight the importance of implementing balanced workload allocation and comprehensive work stress management initiatives to reduce the likelihood of burnout while promoting a healthier and more productive workplace.